The correlation between coagulation biomarkers, bone turnover markers, and bone mineral density in Chinese adults aged ≥ 50 years - Zhengming Wang; Rui Wang; Haiya Ge; Yong Gu; Sicheng Xian; Laijun Yan; Guoqing Du; Zhibi Shen; Shuaijie Lv; Hongsheng Zhan; Zhengyan Li (Archives of Medical Science)
Introduction Osteoporosis patients undergoing surgery often have significant bleeding, which is closely related to coagulation function. This study aimed to assess the correlation between bone turnover markers (BTMs), bone mineral density (BMD), and coagulation biomarkers.